IMPLEMENTASI SMS GATEWAY SEBAGAI SISTEM INFORMASI KEUANGAN SISWA (STUDI KASUS : SMP NEGERI 6 SINGINGI HILIR) - Laraswati, Dewi; Syam, Elgamar (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2019)
The school is one of the many sectors that have experience the development of information technology. Because one of the conditions for raising grades in certain schools is technology based facilities. In this case, SMPN 6 Singingi Hilir require a financial information system that can process student payments, convey information about student finances and can process reports. To overcome these problems need to be made a computerized information system. The research method used is the method of data collection  by means of interviews and observations. While the system development methodology uses SDLC (System Development Life Cycle). Analysis and design tools used are structured data, like use case diagram, sequence diagram, Activity diagram and class diagram. The appilication program used is Java Netbeans IDE and database used is MySQL. The research is expected to produce a financial information system for students who can help optimally.